Parenting practices and behavior problems in preschool children within an intercultural framework - López Rubio, Sonia; Fernández Parra, Antonio; Vives Montero, María Carmen; Rodríguez García, Olga (Anales de Psicología / Annals of Psychology, 2012)
One issue of concern today is the social adjustment of children to their family and school environment. During the last decades, research on educational practices of parents and their influence on the development of children, have increased. This study was designed to examine the effects of migrant origin on parenting and analyse their relationship with behaviour problems amongst preschool children. The sample included 176 preschool children aged between 4 and 5 years, and their parents, divided into two groups according to their origin (Spanish and immigrants). The results showed differences in parenting practices and a greater presence of emotional problems and difficulties in peers’ relationships in preschoolers from immigrant families. It has also highlighted the influence of coercive parenting practices and lower expectations on the presence of children problems, and the role of sociodemographic factors, such as age or educational level, in this relationship.